(untitled) (Research, Society and Development, 2025)
Vegetable production in Brazil faces significant challenges, including foliar diseases, which affect plant quality and productivity. The accurate identification of foliar diseases helps in the development of control strategies that minimize economic and environmental impacts. The objective of the research was to evaluate the incidence of the main foliar diseases that affect vegetables grown in the IFTM teaching project, Uberlândia-MG campus. The evaluations were carried out between the months of October and December 2023. The crops evaluated were: lettuce, beetroot, carrot, cucumber, okra, radish, arugula and tomato. The plants were placed in the field in beds in DBC and data on the incidence of foliar diseases were analyzed and allowed the identification of the most significant diseases and the relationship between climatic conditions and the incidence of pathogens. Radish was the most evaluated crop, 23% of the total. This significant number may indicate the focus on short-cycle vegetables and also the economic and food relevance of radishes in the study region. Cucumber, with only 4% of evaluations, had low representation, which may indicate that this crop is more common in protected crops. Leaf spot, caused by the fungus Cercospora sp., was the one with the highest incidence among the crops analyzed. The work addressed the challenges faced in vegetable production in an integrated and practical way, highlighting the importance of sustainable strategies to reduce diseases and also economic and environmental impacts.